Immediate postoperative cardiac tamponade following robotic lung resection surgery: a case report - Kathryn M. Jan; Anthony Q. Dao; Ravi Joshi; Sreekanth Cheruku; Suzanne Dellaria; Kunal Karamchandani (Frontiers in Anesthesiology)
Cardiac tamponade is a life-threatening emergency requiring immediate diagnosis and treatment to prevent mortality. Development of cardiac tamponade following non-cardiac surgery is rare, and diagnosis may often be overlooked due to low suspicion. Point-of-care ultrasound (POCUS) is an important tool in the perioperative physician's armamentarium. We describe the development of cardiac tamponade following an initially uneventful robotic lung resection surgery and its prompt detection using POCUS. This case highlights the importance of utilizing bedside POCUS during medical emergencies in the immediate postoperative period. We also make an argument for perioperative care management by POCUS-trained physicians.